Kajian Kepatuhan Terapi dan Kualitas Hidup Terkait Kesehatan Pasien DM Tipe II - Ningsih, Riska; Nasif, Hansen; Yelly Oktavia Sari (Poltekkes Kemenkes Riau, 2025)
Diabetes mellitus is a chronic disease requiring long-term management. Adherence is a crucial determinant of therapeutic success, influencing Health-Related Quality of Life (HRQoL). This cross-sectional study aimed to assess therapy adherence and HRQoL in type 2 diabetes mellitus patients, explore their associations with sociodemographic and clinical factors, and determine the correlation between these variables. The study involved 144 respondents at the Internal Medicine Clinic of RSUD HA Thalib in Sungai Penuh City, conducted in June 2024. The MARS-5 questionnaire was used to measure therapy adherence, while the DQoL assessed HRQoL. Results indicated no significant association between sociodemographic and clinical characteristics and therapy adherence. However, occupation, comorbidities, and complications were significantly associated with HRQoL. Chi-square analysis revealed a significant correlation between therapy adherence and HRQoL (p-value = 0.001). In conclusion, this study demonstrates a significant association between therapy adherence and HRQoL in type 2 diabetes mellitus patients.